Management of Penetrating Eye Injury with Intraocular Foreign Body - Andi Cleveriawan Arvi Putra; Andi Arus Victor; Elvioza Elvioza; Ari Djatikusumo; Gita Lisa Andayani; Anggun Ramayundanta (Majalah Oftalmologi Indonesia, 2015)
Background: To report the importance of vitrectomy procedure in penetrating eye injury with retain intraocular foreign body (IOFB) at the proper time. Methods: An observational case report. A 17-year-old man came to hospital and was diagnosed aspenetrating eye injury with retain intraocular foreign body of the left eye. The visual acuity of the left eyewas only 2 meters finger counting. Immediate surgery of scleral buckling, vitrectomy, intraocular foreignbody removal and intravitreal vancomycin-ceftazidime injection were performed on the next day. Results: There were metallic IOFB, retinal vasculitis and focal retinitis seen when vitrectomy wasperformed. One month after vitrectomy, the visual acuity of the left eye has improved to 6/12 with correction. Conclusion: Proper and prompt management of penetrating eye injury could contribute in preserving agood anatomical and functional result. In the existence of IOFB, vitrectomy should be done promptly inthe first surgical window to gain a better resultKeywords: penetrating eye injury; intraocular foreign body